2007
DOI: 10.1097/01.tp.0000296469.78853.83
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous Hepatocellular Carcinoma and Renal Cell Carcinoma in a Liver Transplant Recipient: A Case Report

Abstract: A 52-year-old male with liver cirrhosis secondary to hepatitis virus C, Child-Pugh score of C10, and Model for End-stage Liver Disease score of 20 was listed for liver transplant. During the pretransplant management, an abdominal computed tomography (CT) and magnetic resonance imaging (MRI, Fig. 1) showed a 2.7ϫ2.2 cm mass in the liver and a 1.7ϫ1.2 cm tumor in the right kidney. The liver mass on the CT was hyperdense with the liver parenchyma in the early arterial phase of contrast enhancement and hypodense i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 3 publications
1
8
0
Order By: Relevance
“…Our findings validate previously published reports (10,16) suggesting that older age and African-American race are independent risk factors for RCC. Our findings thus corroborate our own clinical observations and seropositivity data, as well as frequent anecdotal reports in the literature that have strongly suggested an association between chronic HCV infection and RCC (11)(12)(13)(14)17).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings validate previously published reports (10,16) suggesting that older age and African-American race are independent risk factors for RCC. Our findings thus corroborate our own clinical observations and seropositivity data, as well as frequent anecdotal reports in the literature that have strongly suggested an association between chronic HCV infection and RCC (11)(12)(13)(14)17).…”
Section: Discussionsupporting
confidence: 92%
“…Di Micco et al (11) reported a cluster of five cases of RCC developing among HCV patients within a brief time frame and were the first to strongly suggest a renal oncogenic potential for HCV infection. Fayek et al (12) in 2007 reported two cases of coexisting HCV and RCC in liver transplant candidates, and Garcia et al (13) in 2007 reported synchronous hepatocellular carcinoma and RCC in a liver transplant recipient. In 2008 Rifkin (14) described a chronic hemodialysis patient with simultaneous HCV and RCC.…”
Section: Introductionmentioning
confidence: 99%
“…One study showed an incidence of 3.7% of synchronous cancers related to RCC. 1 Such malignancies include urological cancers, esophageal carcinomas, colorectal carcinomas, lung cancer, breast cancer, gynecological cancer, sarcoma and non-Hodgkin's lymphoma. 6 The occurrence of synchronous RCC and HCC is extremely rare.…”
Section: Discussionmentioning
confidence: 99%
“…The coexistence hepatocellular carcinoma (HCC) and renal cell carcinoma (RCC) is extremely rare, and only a few case reports could be found in the literature. 1 …”
Section: Introductionmentioning
confidence: 99%
“…Case reports exist of renal lymphoma [37] and renal cell carcinoma [38] in the setting of CHC. Given the rarity of renal lymphoma, the lack of clear pathophysiologic basis, and the infrequent nature of case reports, the possibility of this being a chance occurrence should be considered.…”
Section: Renal Cell Carcinoma and Lymphomamentioning
confidence: 97%